How to Treat the Exchange Rate Assumption for an Inflation Targeting Regime - Jan F. Qvigstad (Norges Bank, 2005)
The topic I am going to discuss here is how to treat the exchange rate assumption when making projections under an inflation targeting regime. The central bank of Norway made the official change to inflation targeting in March 2001, and my talk is based on our experience since then.
hdl:11250/2508131; Additional information: Summary of talk held at Bank of England's Chief Economists' Workshop in London, April 4th to 6th 2005.
Keywords: 330